PENGARUH JENIS PRODUK DAN LOKASI USAHA TERHADAP KINERJA UMKM DENGAN DIGITAL FINANCIAL TECHNOLOGY SEBAGAI VARIABEL MODERASI (STUDI KASUS UMKM DI KABUPATEN BOJONEGORO) - Afriza, Dwi Sri Dani; Triwibowo, Bambang Sutadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of product type and business location on the performance of micro, small, and medium enterprises (UMKM) in Bojonegoro Regency, as well as examine digital financial technology as a moderation variable in the relationship. Explanatory research with a quantitative approach will be used. The sampling method to be used in this study is purposive sampling. The respondents for this study consisted of 105 UMKM actors in Bojonegoro Regency. Data collection was carried out using questionnaires. Smart PLS type 3.0 will be used for data analysis. The results showed that there was a significant positive influence between product type variables and MSME performance. There is no influence between business location variables and MSME performance. Meanwhile, the relationship between product type, business location, and MSME performance is not moderated by digital financial technology.